A human neurodevelopmental model for Williams syndrome - Chailangkarn, Thanathom; Trujillo, Cleber A.; Freitas, Beatriz C.; Hrvoj-Mihic, Branka; Herai, Roberto H.; Yu, Diana X.; Brown, Timothy T.; Marchetto, Maria C.; Bardy, Cedric; McHenry, Lauren; Stefanacci, Lisa; Järvinen, Anna; et al. (Nature (London), 2016)
A human neurodevelopmental model fills the current knowledge gap in the cellular biology of Williams syndrome and could lead to further insights into the molecular mechanism underlying the disorder and the human social brain. An iPSC model for Williams syndrome Individuals with the neurodevelopmental disorder Williams syndrome (WS) lack a region of about 25 genes on chromosome 7. The condition is characterized by hypersociability and a range of cognitive and behavioural impairments, but how specific genes contribute to the neuroanatomical and functional alterations is not known. Alysson Muotri and colleagues have used cellular reprogramming technologies to generate induced pluripotent stem cells (iPSCs) from individuals with WS and controls. iPSC-derived neural progenitor cells from individuals with WS had increased apoptosis owing to haploinsufficiency of the gene FZD9. In addition, iPSC-derived WS cortical neurons displayed altered activity and morphological changes, some of which matched those seen in postmortem brains of individuals with WS. This human iPSC model may provide insights into the molecular and cellular mechanisms underlying the various features of the disorder. Williams syndrome is a genetic neurodevelopmental disorder characterized by an uncommon hypersociability and a mosaic of retained and compromised linguistic and cognitive abilities. Nearly all clinically diagnosed individuals with Williams syndrome lack precisely the same set of genes, with breakpoints in chromosome band 7q11.23 (refs 1 , 2 , 3 , 4 , 5 ). The contribution of specific genes to the neuroanatomical and functional alterations, leading to behavioural pathologies in humans, remains largely unexplored. Here we investigate neural progenitor cells and cortical neurons derived from Williams syndrome and typically developing induced pluripotent stem cells. Neural progenitor cells in Williams syndrome have an increased doubling time and apoptosis compared with typically developing neural progenitor cells. Using an individual with atypical Williams syndrome 6 , 7 , we narrowed this cellular phenotype to a single gene candidate, frizzled 9 ( FZD9 ). At the neuronal stage, layer V/VI cortical neurons derived from Williams syndrome were characterized by longer total dendrites, increased numbers of spines and synapses, aberrant calcium oscillation and altered network connectivity. Morphometric alterations observed in neurons from Williams syndrome were validated after Golgi staining of post-mortem layer V/VI cortical neurons. This model of human induced pluripotent stem cells 8 fills the current knowledge gap in the cellular biology of Williams syndrome and could lead to further insights into the molecular mechanism underlying the disorder and the human social brain.